(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objectives: The aim of the following study is to determine the pooled prevalence of complications related to diabetes mellites at a tertiary care hospital and to create awareness among junior doctors to further improve the diabetic foot care services in the form of a standards audit. Materials and Methods: This clinical audit was conducted in a cross-sectional pattern and data pertaining to all admitted patients related to diabetes mellites and its complications from the surgical department was collected from July 2024 to December 2024. A total of 125 patients were enrolled, either admitted through OPD or emergency. The variables that were included in the study are the following: name, age, gender, contact number, date of admission, medical record number (MR number), characteristics of diabetic foot ulcer (if present), the treatment given, and the outcome. Data was collected in a pre-designed proforma, added to Microsoft excel sheet and analyzed through SPSS software version 23.0. The data is described in the form of description, charts, and tables. Results: The mean duration of diabetes mellites in years was 4.81 ± 0.132 with most patients falling in the range of 5 years (36%). The mean HbA1c and RBS levels on admission were 7.01 ± 0.44 and 227.8 ± 5.3 respectively. In terms of duration of ulcer formation, 22.4% patients had the ulcer for 5 months, which was the longest. As far as management and outcomes are concerned, just17.6% patients showed compliance with medication, but only 19.2% progressed towards an amputation. Conclusion: The audit has given us a further clue that the prevalence of diabetic foot ulcers in our province is still high. However, effective and timely steps can reduce this complication.